Establishing the Usability of a Virtual Training System for Assembly Operations within the Automotive Industry. Issue 6 (8th August 2016) - Langley, A.; Lawson, G.; Hermawati, S.; D'Cruz, M.; Apold, J.; Arlt, F.; Mura, K.
Abstract: Virtual training systems deliver training within a virtual environment (VE) using virtual reality (VR) or augmented reality (AR) technologies. However, to be fully accepted as a valid tool for training within the automotive industry, evidence is required on the ability of these systems to deliver effective and efficient training to the relevant users. This paper aims to investigate the effectiveness and efficiency of the first prototype of the virtual training system (VTS) developed within the VISTRA (Virtual Simulation and Training of Assembly and Service Processes in Digital Factories) project (FP7‐ICT‐285176), using real end users from the OPEL automotive plant in Rüsselsheim, Germany. Two separate and independent studies were employed that used objective and subjective methods of investigation to establish performance and usability measures. The objective results show that virtual training was effective in reducing error during task performance when compared to traditional training. The subjective results concluded that the opinions of the participants were mainly positive concerning the overall use of the VTS for assembly operation training; however, a number of issues were highlighted and reported to the developers for further advancement of the system.